Development of the indicator’s system for quality controlling vehicles' processes of maintenance and repair - Тарандушка, Людмила Анатоліївна; Одокієнко, Світлана Миколаївна; Тарандушка, Іван Павлович (Technology audit and production reserves, 2016)
The article deals with the system of indicators developed on the basis of vehicle maintenance and repair for the quality control. The system of working environment indicators was detected on the basis of the analysis of maintenance and repair processes. On the basis of a linear regression model and researches the dependence for the degree of importance of each indicator calculation is detected. The analysis found that the proposed system of indicators has properties necessary and sufficient for the assessment of the company for the maintenance and repair of vehicles which include organizational and technical support; production facilities (buildings, structures); technological equipment, accessories; staffing; control and diagnostic, test equipment and means of measurement; regulatory, technical and technological documentation. The parameters of the maintenance and repair of vehicles carry the full amount of information that reflects the requirements of the certification system (or declare). Some of the indicators are found to consist of a number of components. Hence there is a need to describe these indicators by means of their constituents, and then choose the most significant and important for the final result of certification (or declare). The number of components for assessment of the level of performed work of the company is defined for the first time. After selecting the most important and significant component the system of indicators for the final result of certification or declaration is determined. In the result of the research the defined indicators make it possible to compare companies with each other, to assess the whole market for the maintenance and repair of vehicles.